Abrasion Indicators for Smart Surfaces Based on a Luminescence Turn‐On Effect in Supraparticles - Wenderoth, Sarah; Granath, Tim; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Advanced Photonics Research, 2020)
Slight mechanical damage on surfaces or coatings caused, for example, by shear stress, is hardly detectable by simple means. Therefore, shear stress indicator particles for the creation of “interactive and communicating” coatings are presented. These are core-shell supraparticles obtained by a two-step spray-drying assembly process from nanoparticle dispersions. Three different types of nanoparticles are used to create the supraparticles: dye-doped silica nanoparticles responsible for the fluorescence signal, iron oxide nanoparticles acting as a fluorescence absorber, and pure silica nanoparticles regulating the indicator sensitivity. The creation of two different types of indicator systems is feasible by changing the nanoparticle arrangements within the supraparticle: A turn-off and a turn-on system, which indicate—after incorporation into a coating—shear stress by the decrease or the increase in the fluorescence intensity, respectively. Herein, two different mechanisms compete with each other: on the one hand, the change in the fluorescence signal due to physical light-absorbing effects, and on the other hand, the abrasion of luminescent material. The clear superiority of the turn-on system to achieve a reliable signal is demonstrated in this work. With the particle systems, interactive and communicating surface coatings are established.<br

Abrasion Indicators for Smart Surfaces Based on a Luminescence Turn‐On Effect in Supraparticles - Wenderoth, Sarah; Granath, Tim; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Advanced Photonics Research, 2020)
Slight mechanical damage on surfaces or coatings caused, for example, by shear stress, is hardly detectable by simple means. Therefore, shear stress indicator particles for the creation of “interactive and communicating” coatings are presented. These are core‐shell supraparticles obtained by a two‐step spray‐drying assembly process from nanoparticle dispersions. Three different types of nanoparticles are used to create the supraparticles: dye‐doped silica nanoparticles responsible for the fluorescence signal, iron oxide nanoparticles acting as a fluorescence absorber, and pure silica nanoparticles regulating the indicator sensitivity. The creation of two different types of indicator systems is feasible by changing the nanoparticle arrangements within the supraparticle: A turn‐off and a turn‐on system, which indicate—after incorporation into a coating—shear stress by the decrease or the increase in the fluorescence intensity, respectively. Herein, two different mechanisms compete with each other: on the one hand, the change in the fluorescence signal due to physical light‐absorbing effects, and on the other hand, the abrasion of luminescent material. The clear superiority of the turn‐on system to achieve a reliable signal is demonstrated in this work. With the particle systems, interactive and communicating surface coatings are established.<br
Keywords: abrasion indicators; communicating materials; smart surfaces; supraparticles; turn-on fluorescence

An all white magnet by combination of electronic properties of a white light emitting MOF with strong magnetic particle systems - Seuffert, Marcel T.; Wintzheimer, Susanne; Oppmann, Maximilian; Granath, Tim; Prieschl, Johannes; Alrefai, Anas; Holdt, Hans Jürgen; Müller-Buschbaum, Klaus; Mandel, Karl (Journal of Materials Chemistry C, 2020)
A multi-component particle system was developed that combines the properties of white color, white light emission and strong magnetism on the macroscopic and microscopic scale. The system is constituted by combination of an inorganic white core with either hard or soft magnetic properties and a white light emitting MOF. The key towards this achievement is the supraparticulate character constituted by a magnetic core, of either magnetite or α-Fe, surrounded by titania and silica nanoparticles of a certain size in a loose structural shell-arrangement as white components and finally the white light emitting metal-organic framework (MOF) EuTb@IFP-1 as building blocks of a core-shell structure. The supraparticles are created by forced assembly of the inorganic compounds and by combining spray-drying and postsynthetic modification by solvothermal chemistry. Thereby, the gap is bridged that homogenous compounds are either strongly magnetic, white in appearance or white light emitting. The composites presented herein inherit these properties intrinsically as electronic properties. The white characteristics are based on all optical properties that enable white: light reflection, refraction, and light emission. This work shifts the paradigm that strong magnetic materials are always expected to be intrinsically dark. This journal is
CRIS-Team Scopus Importer:2020-12-11

A Single Magnetic Particle with Nearly Unlimited Encoding Options - Müssig, Stephan; Reichstein, Jakob; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl (Small, 2021)
Communicating objects are demanded for product security and the concepts of a circular economy or the Internet of Nano Things. Smart additives in the form of particles can be the key to equip objects with the desired materials intelligence as their miniaturized size improves applicability and security. Beyond their proposed identification by optical signals, magnetic signals deriving from magnetic particles can hypothetically be used for identification but are to date only resolved roughly. Herein, a magnetic particle-based toolbox is reported, that provides more than 77 billion (77 × 109) different magnetic codes, adjustable in one single particle, that can be read out unambiguously, easily, and quickly. The key towards achieving the vast code variety is a hierarchical supraparticle design that is inspired by music: similarly to how the line-up variation of a musical ensemble yields distinguishable overtones, the variation of the supraparticle composition alters their magnetic overtones. By minimizing magnetic interactions, customizable signals are spectrally decoded by the simple method of magnetic particle spectroscopy. A large number of chemically adjustable magnetic codes and the possibility of their remote, contactless detection from within materials is a breakthrough for unexploited labeling applications and pave the way towards materials intelligence.
CRIS-Team Scopus Importer:2021-06-11
Keywords: identification; magnetic supraparticles; markers; tracers

Assembly of Zinc‐Single‐Site‐Containing Silica Nanoparticles to Supraparticle Powders with Destructibility to Serve as Filler and Vulcanization Activator in Rubbers - Wenderoth, Sarah; Milana, Paola; Zimmermann, Thomas; Deues, Moritz; Oppmann, Maximilian; Prieschl, Johannes; Mostoni, Silvia; Scotti, Roberto; Wintzheimer, Susanne; Mandel, Karl (Particle & Particle Systems Characterization, 2024)
SECTIONSPDFPDFTOOLS SHARE Abstract The vulcanization process is widely used in industry for tire manufacturing. Therefore, zinc oxide is commonly utilized as an activator material, but unreacted zinc oxide remains in the final products and can be released into the environment with a significant impact. To reduce the amount of required zinc and to prevent leaching from tire material, zinc single site-containing silica fillers are interesting candidates. In these materials, zinc sites are anchored on the surface of silica nanoparticles through their complexation with functionalized aminosilanes. Based on these, a novel powder sample is prepared via spray-drying. The obtained supraparticles allow for a homogeneous distribution of the filler nanoparticles in the rubber matrix via their disintegration during the incorporation process. All synthesis steps are carried out in ethanol and water, respectively, at very mild temperatures to account for sustainability demands. As core of this study, the role of zinc ions and their amino-complexation in nanoparticle dispersion stability and in supraparticle formation during spray-drying is elucidated. Additionally, the superior performance of supraparticles as activator in rubber vulcanization is demonstrated. These show a higher curing efficiency, leading to lower curing time (−70%), higher torque values (+15%), and improved dynamic mechanical properties compared to the conventional ZnO activato
Keywords: morphology control; rubber nanocomposite; silica nanoparticles; spray-dried supraparticles; surface modification; zinc-activated vulcanization

A Supraparticle-Based Five-Level-Identification Tag That Switches Information Upon Readout - Miller, Franziska; Wintzheimer, Susanne; Prieschl, Johannes; Strauss, Volker; Mandel, Karl (Advanced Optical Materials, 2020)
Product identification tags are of great importance in a globalized world with increasingly complex trading routes and networks. Beyond currently used coding strategies, such as QR codes, higher data density, flexible application as well as miniaturization and readout indication are longed for in the next generation of security tags. In this work, micron-sized supraparticles (SPs) with encoded information (ID) are produced that not only exhibit multiple initially covert identification levels but are also irreversibly marked as “read” upon readout. To achieve this, lanthanide doped CaF2 nanoparticles are assembled in various quantity-weighted ratios via spray-drying in presence of a broad-spectrum stealth fluorophore (StFl), yielding covert spectrally encoded ID-SPs. Using these as pigments, QR codes, initially dominated by the green fluorescence of the StFl, could be generated. Upon thermal energy input, these particle-based tags irreversibly switch to an activated state revealing not only multiple luminescent colors but also spectral IDs. This strategy provides the next generation of material-based security tags with a high data density and security level that switch information upon readout and can be, therefore, used as seal of quality.
CRIS-Team Scopus Importer:2020-12-25
Keywords: multilevel luminescence identification; rare earth doped nanoparticles; security tags; stealth fluorophores; supraparticles

Optically Sensitive and Magnetically Identifiable Supraparticles as Indicators of Surface Abrasion - Wenderoth, Sarah; Müssig, Stephan; Prieschl, Johannes; Genin, Emilie; Heuzé, Karine; Fidler, Florian; Haddad, Daniel; Wintzheimer, Susanne; Mandel, Karl (Nano Letters, 2022)
Identifying and ensuring the integrity of products plays an important role in today's globalized world. Miniaturized information taggants in the packaging surface are therefore required to monitor the product itself instead of applying external labels. Ideally, multiple types of information are stored in such additives. In this work, micrometer-sized core-shell particles (supraparticles) were developed to provide material surfaces with both an identifier and a surface abrasion indication functionality. The core of the supraparticles contains iron oxide nanoparticles that allow identification of the surface with a spectral magnetic code resolved by magnetic particle spectroscopy. The fluorescent silica nanoparticles in the supraparticle shell can be abraded by mechanical stress and resolved by fluorescence spectroscopy. This provides information about the mechanical integrity of the system. The application as surfaces, that contain several types of information in one supraparticle, was demonstrated here by incorporating such bifunctional supraparticles as additives in a surface coating.
CRIS-Team Scopus Importer:2022-05-06
Keywords: abrasion indicator; identification; magnetic particle spectroscopy; supraparticles; surface coatings

Spray-Dried Photonic Balls with a Disordered/Ordered Hybrid Structure for Shear-Stress Indication - Wenderoth, Sarah; Bleyer, Gudrun; Endres, Jakob; Prieschl, Johannes; Vogel, Nicolas; Wintzheimer, Susanne; Mandel, Karl (Small, 2022)
Optical microscale shear-stress indicator particles are of interest for the in situ recording of localized forces, e.g., during 3D printing or smart skins in robotic applications. Recently developed particle systems are based on optical responses enabled by integrated organic dyes. They thus suffer from potential chemical instability and cross-sensitivities toward humidity or temperature. These drawbacks can be circumvented using photonic balls as shear-stress indicator particles, which employ structural color as the element to record forces. Here, such photonic balls are prepared from silica and iron oxide nanoparticles via the scalable and fast spray-drying technique. Process parameters to create photonic balls with a disordered core and an ordered particle structure toward the exterior of the supraparticles are reported. This hybrid disordered–ordered structure is responsible for a color loss of the indicator particles during shear-stress application because of irreversible structural destruction. By adjusting the primary silica particle sizes, nearly all colors of the visible spectrum can be achieved and the sensitivity of the response to shear stress can be adjusted.
CRIS-Team Scopus Importer:2022-10-28
Keywords: disordered/ordered core–shell structures; hybrid materials; photonic balls; shear-stress indicators; supraparticles

Supraparticles with a Mechanically Triggerable Color-Change-Effect to Equip Coatings with the Ability to Report Damage - Wenderoth, Sarah; Eigen, Andreas; Wintzheimer, Susanne; Prieschl, Johannes; Hirsch, Andreas; Halik, Marcus; Mandel, Karl (Small, 2022)

Tuning Magnetic and Photophysical Properties of Luminomagnetic Metal-Organic Framework Composites in an Inverse Core-Satellite Structure - Seuffert, Marcel T.; Granath, Tim; Kasper, Thomas; Maile, Ruben; Pujales Paradela, Rosa; Prieschl, Johannes; Wintzheimer, Susanne; Mandel, Karl; Mueller-Buschbaum, Klaus (ChemPlusChem, 2022)
Luminomagnetic composites have been synthesized that allow for an individual tuning of luminescence intensity, chromaticity and magnetization by combination of superparamagnetic, citrate-stabilized iron oxide nanoparticles with the luminescent MOFs (3)(infinity)[Ln(2)(BDC)(3)(H2O)(4)] (Ln=Eu, Tb; BDC2-=terephthalate). The components are arranged to a concept of inverse structuring compared to previous luminomagnetic composites with MOF@magnetic particle (shell@core) composition so that the luminescent MOF now acts as core and is covered by magnetic nanoparticles forming the satellite shell. Thereby, the magnetic and photophysical properties are individually tuneable between high emission intensity (1.2 center dot 10(6) cps mg(-1)) plus low saturation magnetization (6 emu g(-1)) and the direct opposite (0.09 center dot 10(6) cps mg(-1); 42 emu g(-1)) by adjusting the particle coverage of the MOF. This is not achievable with a core-shell structure having a magnetic core and a dense MOF shell. The composition of the composites and the influence of different synthesis conditions on their properties were investigated by SEM/EDX, PXRD, magnetization measurements and photoluminescence spectroscopy.
CRIS-Team WoS Importer:2023-01-27